2006
DOI: 10.1080/15572536.2006.11832654
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ionizing radiation on spore germination and emergent hyphal growth response reactions of microfungi

Abstract: The accident at the Chernobyl Atomic Energy Station resulted in radiation contamination of large tracts of land and particularly the reactor building itself. Sustained exposure of microfungi to radiation appears to have resulted in formerly unknown adaptive features, such as directed growth of fungi to sources of ionizing radiation. We evaluate here spore germination and subsequent emergent hyphal growth of microfungi in the presence of pure gamma or mixed beta and gamma radiation of fungi isolated from a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 5 publications
2
28
0
Order By: Relevance
“…They concluded that inducible MHMR pathway could be a potential mechanism of adaptive evolution in eukaryotes. These observations might explain the radioadaptive response in fungi described by Zhdanova group (1820), but are an unlikely explanation for the enhanced growth effects of irradiated melanized organisms, which responded within hours.…”
Section: Genetic Effects Of Radiation On Fungimentioning
confidence: 84%
See 3 more Smart Citations
“…They concluded that inducible MHMR pathway could be a potential mechanism of adaptive evolution in eukaryotes. These observations might explain the radioadaptive response in fungi described by Zhdanova group (1820), but are an unlikely explanation for the enhanced growth effects of irradiated melanized organisms, which responded within hours.…”
Section: Genetic Effects Of Radiation On Fungimentioning
confidence: 84%
“…They also observed the same results for responses of fungi from contaminated areas to light (20). However, though the presence of adaptive properties in fungi exposed in the long term to elevated radiation levels are very likely, the limitations of the experimental work reported in (1820) might interfere with the authors’ ability to observe the radiostimulation for fungi from the clean areas as well. For example, the activity of the radioactive sources used in the later studies (1820) was approximately 1,000 lower than used in earlier work (17) which might have been insufficient to promote the hyphal growth.…”
Section: Radiotropism Of Chernobyl-associated Fungimentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, several micro-fungi from irradiated areas are not only radiotolerant but positively attracted by radionuclides (positive radiotropism), being able to grow upon “hot particles” and degrade them [6]. Furthermore, in some cases ionizing radiation has a positive stimulation on spore germination [7]. By contrast, positive radiotropism and stimulation of spore germination by ionizing radiation are not observed in fungi isolated from radioactively clean locations [5].…”
Section: Introductionmentioning
confidence: 99%